Trigeminal Numbness After Intracranial Repair of a Spontaneous Meningoencephalocele of the Lateral Wall of the Sphenoid Sinus - De Jesus, Orlando (Cureus, 2021)
A 58-year-old female with an eight-year history of rhinorrhea and a two-day history of subjective fever, chills, and vomiting presented to the emergency department for neurosurgical evaluation. Brain MRI demonstrated herniation of the meninges and portions of the inferomedial right temporal lobe through a defect of the lateral wall of the right sphenoid sinus, extending to the sphenoethmoidal recess and posterior right ethmoid air cells. A right pterional craniotomy was performed where the herniated part of the right temporal lobe, and its associated meninges, were excised. After surgery, she had hypoesthesia at the right maxillary division of the trigeminal nerve. This finding was caused by the proximity of the trigeminal nerve to the dural dissection that we performed at the bone defect. This rare complication has never been described after intracranial surgery. Only eight literature reports have described hypoesthesia or paresthesia of the trigeminal nerve after endoscopic resection of a sphenoid sinus meningoencephalocele. The patient has not had any recurrence of rhinorrhea after a six-month follow-up period.